PENEGAKAN SANKSI ADMINISTRASI TERHADAP PELANGGARAN DISIPLIN PEGAWAI NEGERI SIPIL DI BADAN PENDAPATAN DAERAH PROVINSI RIAU BERDASARKAN PERATURAN PEMERINTAH NOMOR 94 TAHUN 2021 TENTANG DISIPLIN PEGAWAI NEGERI SIPIL - Rifa Ariqa; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Civil Servants have a very important role in achieving national goals. To achievethese national goals, Civil Servants must have honest and responsible personalities in carryingout their duties. However, there are still employees who violate disciplinary rules so that it caninterfere with performance in their work which is in charge of serving the community. Manyemployees underestimate the regulations regarding the discipline of Civil Servants. In thisstudy, the authors conducted research at Badan Pendapatan Provinsi Riau to see how it wasimplemented, the obstacles encountered, and the efforts that could be made in upholdingdiscipline at the Regional Revenue Agency of Riau Province.This study uses the sociological legal research method, because it directly conductsresearch on the locations or points examined to provide a complete and clear picture of theproblems examined. This research is located in Badan Pendapatan Provinsi Riau with apopulation and sample, namely parties related to the problems studied in this study. Sources ofdata, namely primary data and secondary data, data collection techniques in this study wereobservation, interviews, and literature review. Qualitative data analysis, namely data stated inwriting or verbally and real behavior with deductive conclusions, namely general to specificwithdrawals.Based on the research results, the Regional Revenue Agency for Riau Province usesGovernment Regulation Number 94 of 2021 for discipline enforcement, but in practice it is stillnot appropriate due to obstacles encountered in its implementation such as lack of supervisionfrom authorized officials, weak law enforcement, limited resources people and the fading senseof self-discipline in the Civil Servants themselves. There have been various efforts made indealing with these obstacles such as by carrying out internal coaching regarding discipline,providing advice and directions to employees who violate it, imposing sanctions according tothe violations committed, and there must also be self-awareness from Civil Servants regardingdiscipline.Keywords: Civil Servants, Discipline Violations, Disciplinary Sanctions Enforcement